Modified QUIC protocol for improved network performance and comparison with QUIC and TCP. Issue 1 (2019) - Kharat, Prashant; Kulkarni, Muralidhar
Congestion control mechanism is solely responsible for maintaining the performance of streaming data. However, when there is no congestion, a regular delivery window update is followed as a step by step process. The process can be improved by individual window update along with acknowledgement (ACK) as feedback to the server even in the absence of congestion. To achieve maximum throughput and minimum delay, we have suggested modification in the existing handshaking mechanism of quick UDP internet connections (QUIC) protocol. This paper presents an investigation of QUIC protocol performance and proposes a modified QUIC (ModQUIC): a modification in existing handshaking mechanism of QUIC to reduce control overhead. Chromium server-client model testbed setup results, show that the proposed technique gives stable output and improves performance in terms of overall throughput and delay over QUIC and transmission control protocol (TCP). Performance has been tested for limited (2 Mbps) and sufficient (10 Mbps) link bandwidth in presence of loss. The validation of results has been carried out with the help of linear regression model. The result show a throughput improvement of 35.66% and 51.93% over QUIC and TCP respectively and also the delay is reduced by 3% to 5% over QUIC and TCP.